Organizational Culture Management In Building Educational Innovation of Private Madrasah Aliyah In Riau Province - Junaidi, Roni; Anwar, Kasful; Imron Rosadi, Kemas (International Journal of Education, Language, and Social Science, 2025)
This study explores the concept and management of organizational culture in fostering innovation within Private Islamic Senior High Schools in Riau Province, Indonesia. Employing a qualitative descriptive approach, data were collected through observations, interviews, and document analysis, supported by relevant reference instruments. The findings reveal two key insights. First, the strength of an organizational concept extends beyond its formal structure to include its responsiveness to both internal and external demands. In the context of Private Islamic Senior High Schools in Riau, this is demonstrated by the ability to align national education policies with the local needs of students and communities. The organization’s role as a facilitator of innovation is crucial to ensuring that learning programs are not only routine but also responsive to real-world educational challenges. Second, sustainable educational innovation requires an organizational culture rooted in creativity, risk-taking, and a commitment to continuous improvement. Such a culture can be cultivated through effective leadership, regular collective reflection, and strong collaboration among teachers. Furthermore, strategic management of organizational culture can help overcome structural and psychological barriers that often hinder meaningful change